2023
DOI: 10.3762/bjoc.19.15
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of insect sex pheromones: recent improvements based on iron-mediated cross-coupling chemistry

Abstract: In the current ecological context, use of insect sex pheromones as an alternative to conventional pesticides is in constant growth. In this report, we discuss the recent contributions brought by our groups in the field of iron-catalyzed cross-couplings applied to the synthesis of insect pheromones. The pivotal question of the development of sustainable synthetic procedures involving cheap, non-toxic and efficient additives is also discussed, as well as the mechanistic features guiding the reactivity of such ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…During the past few years, we demonstrated that introduction of insaturations in linear pheromones could easily be done using an iron-catalyzed cross-coupling between alkyl Grignard reagents and alkenyl electrophiles in the absence of any cosolvent or ligand . The key of this approach is to use α, ω-difunctionalized Grignard reagents bearing a magnesium alkoxide terminal group (−OMgX).…”
Section: Introductionmentioning
confidence: 99%
“…During the past few years, we demonstrated that introduction of insaturations in linear pheromones could easily be done using an iron-catalyzed cross-coupling between alkyl Grignard reagents and alkenyl electrophiles in the absence of any cosolvent or ligand . The key of this approach is to use α, ω-difunctionalized Grignard reagents bearing a magnesium alkoxide terminal group (−OMgX).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, total syntheses have also been achieved with enzymes, strengthening the links to biology [15]. Total synthesis is not limited to academic laboratories but rather also pursued in industry, where a particular efficiency and economy of tasks is of paramount importance [12], as illus- trated in this thematic issue with the synthesis of pheromones [16]. This requires permanent technological progress.…”
mentioning
confidence: 99%